Review of techniques in faceted search applications - Mahdi M.N.; Ahmad A.R.; Ismail R.; Subhi M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer networks; Search engines; Data quicker; Exploratory search; Faceted search; Filtering informations; Information overloads; Management method; Multiple dimensions; Information filtering